Antiulcer Activity and Potential Mechanism of Action of the Leaves of Spondias mombin L. (26th April 2018) - Brito, Samara Alves; de Almeida, Cynthia Layse Ferreira; de Santana, Temístocles Italo; da Silva Oliveira, Alisson Rodrigo; do Nascimento Figueiredo, Jéssica Carla Bezerra; Souza, Isis Torres; de Almeida, Lécio Leone; da Silva, Márcia Vanusa; Borges, Augusto Santos; de Medeiros, Jonathan Wagner; da Costa Silva Neto, Jacinto; de Cássia Ribeiro Gonçalves, Rita; et al.
Abstract : Spondias mombin L. is used in folk medicine for the treatment of inflammation and gastrointestinal diseases. Our study investigated the antiulcer activity of S. mombin ethanolic extract (SmEE) and its majority compounds gallic acid (GA) and ellagic acid (EA). Phytochemical characterization was performed by HPLC. The SmEE was screened for in vitro antioxidant activities using phosphomolybdenum, ABTS, DPPH, and FRAP assays. The antiulcer activity of SmEE, GA, EA, or GA + EA was evaluated by gastric lesion models induced by absolute ethanol and indomethacin. Following this, it is capable of stimulating mucus production, antisecretory capacity, and the influence of −SH groups and NO in the effect of SmEE. Its healing activity was demonstrated by acetic acid-induced chronic ulcer model. Anti- Helicobacter pylori activity was assessed by determining the MIC of the SmEE (64–1024  μ g/mL). The HPLC results identified the presence of gallic acid and ellagic acid in SmEE. The extract showed antioxidant activity in vitro. SmEE (50, 100, and 200 mg/kg) reduced the area of ulcerative lesions induced by ethanol in 23.8, 90.3, and 90.2%, respectively. In NSAID model, the SmEE induced protection of 36.8, 49.4, and 49.9%, respectively. GA (10 mg/kg) or EA (7 mg/kg) or the association of GA + EA (10 + 7 mg/kg) inhibited the ethanol-induced lesions in 71.8, 70.9, and 94.9%, respectively, indicating synergistic action. SmEE (100 mg/kg) decreased acid secretion and H + concentration in the gastric contents, increased levels of mucus, and showed to be dependent of −SH groups and NO on the protection of the gastric mucosa. In chronic ulcer model, SmEE reduced the gastric area lesion. SmEE showed anti- H. pylori activity. In conclusion, our study showed that SmEE has antiulcerogenic activity. GA and EA are isolated gastric protectors and, when associated, acted synergistically to protect the gastric mucosa.